2016
DOI: 10.1016/j.otsr.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of stability at more than 12 months of follow-up after anterior cruciate ligament reconstruction using all-inside quadruple-stranded semitendinosus graft with adjustable cortical button fixation in both femoral and tibial sides

Abstract: Prospective study - Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
4
28
1
Order By: Relevance
“…Our results confirm the hypothesis that the outcomes of the novel adjustable CSF device compare favorably with those reported in the literature for fixed-length CSF devices § and with those of other adjustable CSF devices 8,10,11,15,23,57,68 (Table 6). While most published studies reported anteroposterior laxity measured using different techniques and forces, our series was measured using one of the most reproducible systems (GNRB), 9,31,53 which applied a constant calibrated force of 150 N. Our postoperative anterior laxity was considerably lower than most values reported in the literature, including series that measured laxity at lower forces.…”
Section: Discussionsupporting
confidence: 88%
“…Our results confirm the hypothesis that the outcomes of the novel adjustable CSF device compare favorably with those reported in the literature for fixed-length CSF devices § and with those of other adjustable CSF devices 8,10,11,15,23,57,68 (Table 6). While most published studies reported anteroposterior laxity measured using different techniques and forces, our series was measured using one of the most reproducible systems (GNRB), 9,31,53 which applied a constant calibrated force of 150 N. Our postoperative anterior laxity was considerably lower than most values reported in the literature, including series that measured laxity at lower forces.…”
Section: Discussionsupporting
confidence: 88%
“…Careful interpretation of the many published studies shows that the limit of 3 mm has also been exceeded in some of their patients. 7,22,27,32 In a recent large randomized clinical trial, Mohtadi et al 32 compared the results of ACLR by using single-bundle and double-bundle hamstring autografts and patellar tendon autografts. In all cases, a fixed-loop Endobutton was used for femoral fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study had much better mean Lysholm score (92.96 ± 6.00) with no patient showing poor outcome. This may be the result of using interference screw fixation on tibial side which is a stronger fixation modality as compared to extracortical tibial fixation [23,24] . Nakamura et al studied active knee flexion and hamstring strength after ACL reconstruction and observed significant difference in knee flexion torques at deeper flexion angles between ST4 and STG groups [18] .…”
Section: Discussionmentioning
confidence: 99%